Retrospective study: Neutrophil-to-lymphocyte ratio for distinguishing pulmonary tuberculosis and community-acquired pneumonia in children - Djiu, Wina; Setyoningrum, Retno Asih; Andarsini, Mia Ratwita (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Tuberculosis and pneumonia remain among the top ten causes of death in children under five. Clinical manifestations of pulmonary TB in children are mostly nonspecific and resemble acute pneumonia. The paucibacillary nature of TB in children contributes to diagnostic challenges. The neutrophil-to-lymphocyte ratio (NLR) is a straightforward biomarker that connects the innate and adaptive immune systems. This study aims to analyze the effectiveness of the NLR in distinguishing pulmonary tuberculosis (TB) from community-acquired pneumonia (CAP) in children.Methods: This research is a retrospective case-control observational study based on medical record data of pediatric subjects with pulmonary TB or CAP treated at RSUD Dr. Soetomo. Characteristics and laboratory data were collected from medical records.Results: A total of 50 subjects with pulmonary TB and 50 subjects with CAP demonstrated a significantly lower NLR in the pulmonary TB group (median 1.31; 0.23–5.62) vs. the CAP group (median 3.98; 1.19–53.51), p